The Macroeconomics of Specificity - Caballero, Ricardo J.; Hammour, Mohamad L. (Journal of Political Economy, 1998)
Specific quasi rents arise in a variety of economic relationships and are exposed to opportunism unless fully protected by contract. Rent appropriation has important macroeconomic consequences. Resources are underutilized, factor markets are segmented, production suffers from technological “sclerosis,” job creation and destruction are unbalanced, recessions are excessively sharp, and expansions run into bottlenecks. While, depending on the shock, expansions may require reinforcement or stabilization, recessions should typically be softened. In the long run, institutions may evolve to alleviate the problem by balancing appropriation. Technology choice will also be affected, with the appropriated factor partially “excluding” the other from production to reduce appropriation.